2004
DOI: 10.3102/01623737026001039
|View full text |Cite
|
Sign up to set email alerts
|

State Policies and Equal Opportunity: The Example of Gifted Education

Abstract: This study explores the relationship between state policies, including state mandates and state aid allocations, and the distribution of educational opportunities. Specifically, we analyze the availability of and participation rates in programs for gifted and talented students using data from the Common Core of Data 1993–94 and the Schools and Staffing Survey 1993–94. Analyses herein suggest that program mandates and funding may be effective tools for increasing the distribution of opportunities for gifted chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…It extends previous findings (Baker, 2001a(Baker, , 2001bBaker & Friedman-Nimz, 2004) that equity and access in gifted education should include examination of potential disparities in services provided to identified gifted students. This study examined variables previously found associated with variance in funding and staffing gifted education, but the present study also included the examination of the effect of locale (city, suburb, town, rural) on students' opportunities in gifted education programs.…”
Section: Discussionsupporting
confidence: 83%
“…It extends previous findings (Baker, 2001a(Baker, , 2001bBaker & Friedman-Nimz, 2004) that equity and access in gifted education should include examination of potential disparities in services provided to identified gifted students. This study examined variables previously found associated with variance in funding and staffing gifted education, but the present study also included the examination of the effect of locale (city, suburb, town, rural) on students' opportunities in gifted education programs.…”
Section: Discussionsupporting
confidence: 83%
“…Although prior studies of policy in gifted education have focused primarily at the state level (e.g., Baker & Friedman-Nimz, 2004), we suggest here that decisions at the local (district) level can have a profound impact even within relatively narrowly prescribed state guidelines such as those in Florida. Here too, a handful of prior studies have examined outcomes associated with gifted program advocacy at the local level, within single districts (e.g., Grantham, 2003), but we suggest that additional research across districts is needed to increase rates of identification and provision of appropriate services for students from groups that traditionally have been underserved in gifted programs.…”
Section: Discussionmentioning
confidence: 98%
“…Not surprisingly, Baker and Friedman-Nimz (2004) found that schools in states with policy mandates for gifted education were 2 to 2.7 times as likely to offer gifted programs as schools in states without mandates. Swanson (2007) echoed these findings in a case-study investigation of the formation and implementation of new state policy in the state of South Carolina.…”
Section: State-level Mandates and Fundingmentioning
confidence: 99%
“…Additionally, Baker and Friedman-Nimz (2004) found that schools with a higher percent of low-income children were less likely to offer a gifted education program, and of the schools offering services, the gifted program served a lower percentage of the overall student population in those schools.…”
Section: Identification Policies and Practicesmentioning
confidence: 99%
See 1 more Smart Citation